2017
DOI: 10.11114/ijsss.v5i6.2304
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and Innovation of Mushroom Business in Rural Area Indonesia: Case Study of a Developed Mushroom Enterprise from Cianjur district, West Java, Indonesia

Abstract: Mushroom farming has become attractive business in agricultural sector due to its simplicity and flexibility of cultivation and quite profitable. Health awareness of Indonesian people about mushroom gives a positive impact to mushroom business. Behind the good aspects, several evidence argued that production performance of mushroom business is not optimal related to less capacity and deficiently appropriate knowledge. This paper aims to learn the unique strategy and innovation from local mushroom enterprise wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…All of activities employees depend on the training, because training is an activity to improve the ability, form skills and improve the performance of individuals or groups in performing their duties by improving skills, knowledge, skills, attitudes and behaviors that are specific to the needs or job [24]. The strategies were capable of being successful innovation by interacting and cooperating with external sources, and performing certain adjustment with local condition [1].…”
Section: Fig1 Strategy Of Entrepreneurship Management Of Oyster Musmentioning
confidence: 99%
“…All of activities employees depend on the training, because training is an activity to improve the ability, form skills and improve the performance of individuals or groups in performing their duties by improving skills, knowledge, skills, attitudes and behaviors that are specific to the needs or job [24]. The strategies were capable of being successful innovation by interacting and cooperating with external sources, and performing certain adjustment with local condition [1].…”
Section: Fig1 Strategy Of Entrepreneurship Management Of Oyster Musmentioning
confidence: 99%
“…The implementation of oyster mushroom agribusiness in Indonesia requires strengthening the adoption of cultivation technology and post-harvest processing, institution strengthening, management optimization, and the use of production factors (Mabuza et al 2012;Iriantinah, 2014;Li and Hu, 2014;Febrianda and Tokuda, 2017). Farmers' willingness to starting oyster mushroom agribusiness is influenced by marital status, formal education, farmer group membership, mushroom consumption level, market availability, farming experience, and land area (Ongoche et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some researches related to the development strategy for oyster mushroom agribusiness have been carried out by researchers (Iriantinah, 2014;Li and Hu, 2014;Dimyati and Astarina, 2016;Fatria, 2017;Febrianda and Tokuda, 2017;Ongoche et al 2017). The purpose of this research is to determine priority factors in the development of sustainable oyster mushroom agribusiness with OPEFB as the growing media.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study identified specifically such aspects as the inadequate support for production and the deficient market support as the obstacles on the dissemination and adoption effort of mushroom farming (Pradhan & Nayak, 2014). We found and suggested that a partnership between enterprise and rural society is an alternative strategy to overcome those obstacles as enterprise has both the technical capabilities and market access (Febrianda & Tokuda, 2017). Partnership can assist farmers in applying good agricultural standards and production as well as reduce the constraints in accessing the markets (Bitzer et al, 2013;Dentoni et al, 2016;Royer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have shown the local champion of mushroom enterprise from Cianjur district which has successfully introduced innovations. This enterprise not only improves the reliability of its artificial medium technology but also implements a partnership to expand its business and to empower the local society (Febrianda & Tokuda, 2017). West Java province occupied the first rank of mushroom production with a total production of 25,194,471 kg or about 67% of national mushroom production in 2014 (Badan Pusat Statistik Kabupaten Cianjur, 2015).…”
Section: Mushroom Farming Development and Mushroom Farming Partnershimentioning
confidence: 99%